Synthesis of complex oxides Eu2О3–Gd2О3–Zr(Hf)О2 using microwave radiation and study of their properties - N. V. Grechishnikov; E. E. Nikishina (Тонкие химические технологии)
Objectives. The authors synthesize complex oxide phases of the composition Eu2−xGdxZr2O7 and Eu2−xGdxHf2O7 at x = 0.5, 1.0, 1.5 under microwave heating conditions and investigate their phase composition, particle size distribution, and specific surface with the purpose of obtaining bulk ceramic materials on their basis and study their behavior when heated to 1473 K.   Methods. Using X-ray phase analysis, the phase composition of samples subjected to heat treatment at temperatures of 1473 and 1773 K was studied, and the cell parameters were calculated. The particle size of the obtained powders was analyzed by laser diffraction on a Fritsch Analysette 22 device. The specific surface area was studied by the Brunauer–Emmett–Teller method on a TriStar 3000 analyzer. Bulk ceramic materials were obtained by cold pressing with subsequent sintering at 1773 K. The coefficient of thermal expansion (CTE) of ceramic samples was studied on a Netzsch DIL 402C dilatometer in a temperature range of 300–1473 K.   Results. At a temperature of 1473 K, all synthesized samples were observed to form a fluorite structure; at a temperature of 1773 K, samples with the composition Eu2−xGdxHf2O7 had an ordered pyrochlore structure. With an increase in the gadolinium content in the samples, a decrease in both the unit cell parameter and the CTE was observed. The particle size of almost all samples did not exceed 100 μm; the specific surface area did not exceed 1 m2/g.   Conclusions. For the first time, compounds with the composition Eu2−xGdxZr2O7 and Eu2−xGdxHf2O7 were obtained using microwave processing at x = 0.5, 1.0, 1.5. As well as determining the dependence of the phase composition on the heat treatment temperature after microwave exposure, the dependence of the change in the unit cell parameters on the gadolinium content in the sample was studied, the particle size distribution was investigated. The CTEs of bulk ceramic samples obtained by cold pressing were additionally studied. The obtained data can be used in the development of thermal barrier coatings and technical ceramics used at high temperatures (up to 1473 K).